2021
DOI: 10.1016/j.envpol.2020.115806
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 in water services: Presence and impacts

Abstract: The occurrence of human pathogenic viruses in aquatic ecosystems and, in particular, in internal water bodies (i.e., river, lakes, groundwater, drinking water reservoirs, recreational water utilities, and wastewater), raises concerns regarding the related impacts on environment and human health, especially in relation to the possibility of human exposure and waterborne infections. This paper reviews the current state of knowledge regarding severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(70 citation statements)
references
References 88 publications
0
59
0
11
Order By: Relevance
“…SARS-CoV-2 can resist standard disinfection treatments such as sodium hypochlorite and at an eco-friendly reduced concentration of free chlorine [176][177][178]. This is reflected by high levels of SARS-CoV-2 (0.05-1.87 × 10 4 /L present in wastewater even after treatment with sodium hypochlorite, perhaps due to the virus being embedded in faecal particles [179] or in association with other resistant microbes [180].…”
Section: Wastewater Monitoring and Surveillance For Sars-cov-2mentioning
confidence: 99%
“…SARS-CoV-2 can resist standard disinfection treatments such as sodium hypochlorite and at an eco-friendly reduced concentration of free chlorine [176][177][178]. This is reflected by high levels of SARS-CoV-2 (0.05-1.87 × 10 4 /L present in wastewater even after treatment with sodium hypochlorite, perhaps due to the virus being embedded in faecal particles [179] or in association with other resistant microbes [180].…”
Section: Wastewater Monitoring and Surveillance For Sars-cov-2mentioning
confidence: 99%
“…Lahrich et al (2021) Global study The occurrence of COVID-19 has been shown in stool samples from symptomatic and asymptomatic people as well as in municipal wastewaters worldwide. Langone et al (2021) Italy COVID-19 was already circulating in northern Italy at the end of 2019; wastewater (sewage) monitoring could contribute to the early detection of this viral circulation. La Rosa et al (2021) Global study COVID-19 in wastewater treatment, sanitation status and health-care infrastructure from middle-and low-income countries was correlated with risk associated with the fecal-oral transmission route.…”
Section: Chinamentioning
confidence: 99%
“…Water safety starts with the protection of water resources in the catchment, therefore it is mandatory to prevent surface and groundwaters from coming into contact with fecal material. It is expected that groundwater benefits from the pathogens removal due to soil filtration, adsorption on sediment grains and progressive inactivation, and viruses in surface waters are exposed to several potentially inactivating stressors, including sunlight, oxidants, and predation by microorganisms (Langone et al, 2021). Rimoldi et al (2020) detected viral RNA in three receiving rivers in the Milan area indicating the partial efficiency of the sewage system of the metropolitan area.…”
Section: Introductionmentioning
confidence: 99%